Child health status - the future of the country (part 2) - Yu.G. Antipkin; A.P. Volosovets; V.G. Maidannik; V.S. Berezenko; R.A. Moiseenko; O.V. Vygovskaya; S.P. Krivopustov; V.N. Zabolotko; N.L. Aryaev; A.E. Abaturov; T.A. Kryuchko; G.V. Beketova; et al. (Zaslavsky O.Yu., 2018)
The article deals with the problems of increasing the incidence and prevalence of childhood diseases during 1994-2016 against the background of a global reduction in the staffing of children's specialists by 1.7 times, with an extremely inadequate supply of the regions of the South-East, Donetsk and Luhansk regions. All of this has a negative impact on the proper medical care of the child population, including the detection of childhood diseases. The authors substantiate the need to restore the personnel and material-technical potential of the pediatric service, the development of modern diagnostic and treatment technologies, the preservation of immunization and the prevention of disability of common childhood diseases that is an important component of the national health care and safety system of the country as a whole.